KONSEP KESETARAAN GENDER DALAM ISLAM: STUDI ANALISIS PEMIKIRAN ZAKIR NAIK - M. Anzaikhan; Sufrizal; Fitri Idani (Pusat Studi Gender dan Anak, 2023)
According to Zakir Naik, although Islam is a teaching that has been practiced since-14 centuries ago, the concept of equality offered is still relevant to be practiced today. Zakir Naik said; the idea of gender equality, which has been popularized by the West recently, is something new and out of their practice in the past. In contrast to the concept of Islam which always spreads the value of equality in various conditions and opportunities. This article belongs to literature research with a qualitative approach. The methodology used is a descriptive analysis study of Zakir Naik's work. The study results conclude that Zakir Naik disagrees with the concept of gender equality promoted by the West, which is considered liberal and uncontrollable. The idea of gender equality offered by Islam is how the rights and obligations between men and women remain balanced according to their respective functions and roles as long as they do not violate Islamic law and ethics.